2012
DOI: 10.2223/jped.2183
|View full text |Cite
|
Sign up to set email alerts
|

Functional state of CD4+ and CD8+ T lymphocytes and their role in the slow progression of HIV infection in pediatric patients

Abstract: Objective: To evaluate simultaneously the functional state of CD4+ and CD8+ T lymphocytes from Venezuelan HIV-1-infected pediatric patients. Methods:Children were assigned to subgroups of rapid progressors (RPs) and slow progressors (SPs), based on clinical features. To determine the degree of CD4+ and CD8+ T-lymphocyte functionality, flow cytometry techniques were used, and diverse parameters of the functionality of these cells were characterized by ex vivo tests, such as expression of CD95/ Fas and CD127, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Children infected with HIV by vertical transmission, according to a recent study, exhibit a bimodal clinical progression. Thus, 10-30% of patients, called rapid progressors, begin to show symptoms of AIDS in their first year of life, and a small group of patients, called slow progressors, remain asymptomatic for many years and can even reach school age unaffected [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Children infected with HIV by vertical transmission, according to a recent study, exhibit a bimodal clinical progression. Thus, 10-30% of patients, called rapid progressors, begin to show symptoms of AIDS in their first year of life, and a small group of patients, called slow progressors, remain asymptomatic for many years and can even reach school age unaffected [8]. …”
Section: Discussionmentioning
confidence: 99%
“…This pleiotropic cytokine is crucial for the development and homeostasis of T-cells, promotes antigen-specific expansion and memory formation (4144), and can reverse T-cell exhaustion (45). Immune failure in both adult and pediatric HIV infection is associated with perturbations in IL-7 signaling (46, 47) and reduced responsiveness (48, 49). In adult long-term non-progressors, IL-7R (CD127) expression is preserved on central memory and effector memory CD4 T-cell compartments when compared to untreated progressors (50).…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of HIV infection, the immune system may not be seriously damaged and may be in the condition of stress response state. During such phase, uncontrolled replication of HIV-1 infection leads to activations of the CD8 + T lymphocytes (which can inhibit HIV replication by cytolytic and noncytolytic responses) and increases the concentration of cytokines such as IFN- γ and IL-10 [ 42 , 43 ]. Earlier studies demonstrated a correlation of maintaining the CD8 + T lymphocyte immune profile with a slow progression of HIV-1 infection [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%